KEAWETAN LIMA PULUH JENIS KAYU TERHADAP UJI KUBURAN DAN UJI DI LAUT - Mohammad Muslich; Sri Rulliaty (BRIN Publishing, 2013)
Fifty wood species collected from Indonesian forest regions were tested according to graveyard test standard and sea water exposure. Wood samples with dimensions of 60 x 5 x 5 em were prepared for graveyard test in Cikampek and 30 x 5 x 2.5 cm for sea water exposure in Rambut Island test area. The results show that in general wood species tested are susceptible to termite attack. Forty seven wood species out of 50 species tested (94%) were positively attacked by termites. Twenty eight species (56%) are classified into natural durability class V, 15 species (14%) are classified into natural durability class IV and 7 species are classified into natural durability class III. One species, Blumeodendron tundifolium was attacked not only bry termite but also suffers by decaying fungi. Another 5 species: Erythrina fusca, Litsea roxburghii, Myristica subaculata, Stercularia oblongata and Trichodenia phillipinensis were also attacked by termites and fungus simultaneously. Sea water exposure test shows that almost all wood species tested were attacked by marine borers. Four wood species (8%) are moderately resistant and classified as natural durability class II, and 12 species (24%) are not resistant and classified as natural durability class IV, while 50 wood species (64%) are classified as perishable and classified as durability class V against marine borers. Only two wood species: Azadirachta indica and Parinari corymbosa arv dassified as durability class II. Marine borers attacked the wood samples include: Martesia striata (Pholadidar family). Teredo bartschi. Dicyathifer manni and Bankia ceba (Teedinidae family).